The Effect of Resin Injection on the Productivity of Shallow Sandstone Layer in Mawar Field - Catur Sunawan Balya; Muhammad Taufiq Fathaddin; Rachmat Sudibjo (Penerbitan Universitas Trisakti, 2019)
Mawar Field is located in North Kalimantan Province. The field has an unconsolidated sandstone layer which is located in Tarakan formation. Porosity of the layer is more than 20%, while permeability of that is between 100 mD and 1000 mD. The zone which is poorly cemented is a source of sand problem. This sand production has an effect on the stability of oil and gas production. Sand production results in the formation of channeling around cement bonding. Sand production problem can be reduced. To overcome the acidity of the shallow formation, it can be done in two ways, that is Gravel pack using propan and stimulation using resin where the sand will be retained behind the formation. In research that has been done using core data and produced sand samples where the results obtained information about the characteristics of sand in shallow zones so that the appropriate treatment method can be recommended that is stimulation with resin. In the use of this resin there will be a permeability reduction of 15% -27% and a maximum fow rate reduction of 20%.